Accuracy of conventional FE-Models in Bulk-Forming of Micropins from Sheet Metal - Kraus, Martin; Hufnagel, Thomas; Merklein, Marion (Journal of Micro and Nano-Manufacturing, 2019)
LFT Import::2019-07-29 (2357)

Accuracy of Conventional Finite Element Models in Bulk-Forming of Micropins from Sheet Metal - Kraus, Martin; Hufnagel, Thomas; Merklein, Marion (Journal of Micro and Nano-Manufacturing, 2019)
The ongoing miniaturization trend in combination with increasing production and functional volume leads to a rising demand for metallic microparts. Bulk forming of microparts from sheet metal provides the potential for mass production of those components by an extensive simplification of the handling. The advantage of a high production rate contrasts with the disadvantage of a low utilization of material. In this context, it is necessary to investigate suitable measures to increase the material utilization. To save cost intensive trial and error tests, numerical analysis could be an appropriate method for a basic process investigation. In this work, a validation with experimental results in the macro- and microscale was used to investigate the eligibility of the finite element method (FEM) for a basic process analysis. For a high transferability, the finite element (FE) models were validated for various tribological conditions and material states. The results reveal that there is a high agreement of the experimental and numerical results in the macroscale. In microscale, conventional FEM shows inaccuracies due to the negligence of size effects in the discretization of the process. This fact limits the application of conventional FE-programs. Furthermore, the results show that lubricated and dry formed blanks lead to the same friction force and process result in the microscale. In addition, the basic formability of the prestrengthened pins in further forming stages was experimentally demonstrated.
CRIS-Team Scopus Importer:2019-05-02
Keywords: bulk microforming; friction; Microforming; micropart; size effects; validation

Analysis of the Part Quality and Process Stability when Producing Metallic Micro Parts by Multi-Stage Bulk Forming from Sheet Metal - Kraus, Martin; Merklein, Marion (Key Engineering Materials, 2022)
Miniaturization of parts for technical products is an ongoing trend across all industries over the past decades. Due to the large number of possible applications, several billion micro parts are produced every year. In mass production, cold forming offers technological, economical and ecological benefits in comparison to other manufacturing methods. Unfortunately, due to size effects that negatively influence the part geometry, the process stability, the handling and the tool stress, this manufacturing technology is currently barely used. Previous research results have shown that bulk microforming from sheet metal has the potential to reduce the aforementioned restrictions decisively. Within this paper, a three-stage bulk microforming process from sheet metal is experimentally analysed to form a demonstrator geometry with dimensions in the sub-millimetre range in all spatial directions. In the first stage, material is provided in form of a pin for subsequent forming stages. During the second stage, a cup geometry is formed on the pin. Finally, the micro part is separated from the sheet metal by shear cutting. To ensure a wide range of applications, the investigations are carried out with copper, steel and aluminium material. This study is focused on the evaluation of the achievable part quality and the process stability. For the evaluation of the geometry and the surface quality, the micro parts are optically measured with a three-dimensional surface measuring system. The standard deviation of the part dimensions and the process forces are used to investigate the influence of size effects in relation to the material and the grain structure.
CRIS-Team Scopus Importer:2022-11-04
Keywords: Bulk microforming; Metallic micro parts; Pin extrusion; Sheet metal; Size effects

Analytical friction force compensation of flow curves out of layer compression tests with the pin extrusion test - Lenzen, Matthias; Kraus, Martin; Merklein, Marion (International Journal of Material Forming, 2020)
For conventional material models like Yld2000-2d or BBC05 the equi-biaxial yield strength is required for the parameter identification. In this context, a commonly used test setup is the hydraulic bulge test. However, an inaccuracy in the characterization of the initial yield strength is present in the hydraulic bulge test. Due to the evaluation of the resulting curvature of the specimen, that is nearly infinite at the onset of yielding, the calculated stress can significant vary. Another proposed test setup for the characterization of the equi-biaxial stress state is the layer compression test. Here, the onset of yielding can be characterized with sufficient accuracy. The disadvantage in this test is the friction between stack and tool that leads to an overestimation of the flow curve. Thus, robust and experimental based friction compensation should be used, to gain a comparable hardening behaviour as in the hydraulic bulge test. In this contribution, the friction in the layer compression test is compensated by characterization of the tribological conditions. Thus, the tribological system consisting of workpiece surface, tool surface and lubricant is characterized using pin extrusion tests. The friction is analysed for the two steel grades DC06 and DP600 and the aluminium AA5182. With the identified friction factors, the measured testing force in the layer compression test is reduced by the portion of friction. For verification, hydraulic bulge tests, which are approximately friction free, are performed and compared with the resulting flow curves of the layer compression tests. Results confirm, that a friction compensation of the layer compression tests lead to a significant improvement of the resulting material parameters in comparison to the hydraulic bulge tests. Additional, a new method for the friction factor characterization is presented that uses in the stress difference of flow curves characterized in hydraulic bulge tests and layer compression tests.
CRIS-Team Scopus Importer:2020-05-12
Keywords: Friction compensation; Layer compression test; Material characterization; Pin extrusion test

Bulk Microforming from Sheet Metal—A Promising Approach for the Mass Production of Cold-Formed Metallic Micro Parts - Kraus, Martin; Merklein, Marion (Minerals, Metals and Materials Series, 2021)
Every year billions of micro parts are produced. In mass production, cold bulk forming offers considerable technological, economical, and ecological potentials compared to alternative production methods. Due to the occurrence of scale effects, high tool stresses, and handling problems, cold bulk forming is not used for the mass production of multi-stage formed metallic micro parts. Within this paper, multi-stage bulk microforming from sheet metal is investigated on the laboratory scale with the material Cu-OFE. Throughout this process, the sheet metal strip serves both as a semi-finished product and as a handling aid. In the first forming stage, a pin is extruded from sheet metal, which is then extruded in a cup during the second stage. For the identification of size effects and the evaluation of such effects on the part quality, the tests are carried out on macro- and micro-scale. In the first step, the process-influencing variable of the blank holder pressure is investigated in the first forming stage in order to derive measures for the highest possible material utilization. The two-stage forming of the pin with cup is compared with a single-stage process to assess the part quality and material utilization depending on the process strategy. Using the correct geometric scaling, size effects are identified and their effects on the forming process are evaluated. The experimental results reveal that it is possible to fabricate micro parts with a diameter of 470 µm and a minimum wall thickness of 36 µm reproducible by using the presented cold bulk microforming process strategy.
CRIS-Team Scopus Importer:2021-09-03
Keywords: Bulk microforming; Material flow; Metallic micro parts; Pin extrusion; Sheet metal; Size effects

Bulk Microforming from Sheet Metal—A Promising Approach for the Mass Production of Cold-Formed Metallic Micro Parts - Kraus, Martin; Merklein, Marion (Proceedings of the 13th International Conference on the Technology of Plasticity, 2021)

Characterization and Modelling of Sheet Material with Graded Strength for More Accurate Finite Element Analysis - Lenzen, Matthias; Kraus, Martin; Merklein, Marion (Key Engineering Materials, 2022)
Many sheet materials do not exhibit constant properties over the sheet thickness. On the one hand, this can be caused by a rolling process with a pass reduction of 1-2%, the so-called skin pass rolling. This is mainly used for deep drawing steel grades to eliminate the pronounced yield strength of the base material. Another possibility is abrasive blasting or shot peening of sheet metal. This causes plastic deformation of the sheet surface and material strengthening. The grading can be used to locally strengthen components or locally adapt the roughness. Since many production processes today are designed numerically, the mapping of such a grading is necessary but currently not implemented in FE code. The aim of this research is, to correlate the material hardness to a plastic pre-strain with a newly developed characterization method. For this purpose, graded material properties are generated by means of abrasive blasting as an example process. The resulting locally varying work hardening over the sheet thickness is further integrated in finite element analysis by the assignment of a starting condition of a 2d-shell element formulation. With this approach, it is possible to map the graded material properties easily in FE simulations with a very good accuracy.
CRIS-Team Scopus Importer:2022-11-04
Keywords: abrasive blasting; Graded material properties; material modelling; sheet metal forming

Characterization of sheet metal components by using an upsetting test with miniaturized cylindrical specimen - Hetz, Peter; Kraus, Martin; Merklein, Marion (CIRP Annals - Manufacturing Technology, 2022)
Especially for safety-relevant components local characterization of the mechanical properties is necessary for product testing. For sheet metal parts with a complicated geometry conventional specimens for standardized tests cannot be extracted due to size limitations. Thus, a novel extraction procedure of miniaturized upsetting specimens is investigated. Taking a miniaturized upsetting specimen out of the sheet component allows for the first time the characterization of sheet metals in a standardized upsetting test under uniaxial compression stresses. Furthermore, this enables the analysis of strain hardening behavior of components and a direct validation of finite element simulations based on the true stress.
CRIS-Team Scopus Importer:2022-08-12
Keywords: Material characterization; Metal forming; Wire EDM

Contact pressure-dependent friction characterization by using a single sheet metal compression test - Kraus, Martin; Lenzen, Matthias; Merklein, Marion (Wear, 2021)
Tribology has a major impact on process stability, product quality and tool life in metal forming processes. Today, the complex system of friction is simplified by the Coulomb friction coefficient or friction factor model for analytical and numerical process analysis. These friction values are determined in laboratory tests and assumed to be constant. Due to smoothing of the surface, displacement of lubricant from the active joint and locally different relative velocities, the friction state changes while forming. To achieve a high accuracy of finite element analysis, it is essential to consider these changing boundary conditions. Identifying strain-dependent friction coefficient or friction factor models by conventional characterization tests, such as the pin extrusion test or ring compression test, require a high number of experiments. Besides that, these tests are not suitable for low plastic strains due to their poor sensitivity. The sheet metal compression test, analyzed in this contribution, enables the description of the strain and contact pressure dependent progression of the friction values in one simple experimental setup. To determine the friction coefficients, the experimentally measured force-displacement curves will be assigned to friction coefficients in a numerically determined nomogram. The calibration of the nomogram is done analytically for the friction-free condition by using the flow curve determined in the uniaxial tensile test. The sheet metal compression test reacts sensitive to changes of the tribological system due to the high ratio of surface to specimen volume and the direct measuring of the press force as an evaluation quantity. The characterization of friction value progression is done for the materials DP600, DC06, Cu-OFE and CuZn30 with different tribological conditions. The results confirm that the friction values and thus the friction condition is changing during the forming process. Additionally, the validity limit of the friction coefficient model can be easily identified by analysing the friction coefficient progression.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Contact mechanics; Contact pressure dependent friction model; Friction progression; Tribology; Tribophysics

Determination of the biaxial anisotropy coefficient using a single layer sheet metal compression test - Hetz, Peter; Lenzen, Matthias; Kraus, Martin; Merklein, Marion (19th International Conference on Sheet Metal, SheMet 2021, 2021)
Keywords: Anisotropy; Metal forming; Material characterization

Erratum: “Potential of joining dissimilar materials by cold formed pin-structures” (Journal of Materials Processing Tech. (2020) 283, (S0924013620301114), (10.1016/j.jmatprotec.2020.116697)) - Kraus, Martin; Merklein, Marion (Journal of Materials Processing Technology, 2021)
The publisher regrets that the below images appear incorrectly in the original article. Figure 3 should appear as follows:
CRIS-Team Scopus Importer:2021-05-14

Experimental Evaluation of the Feasibility and Reproducibility of a Novel Multi-step Forming Process for Cu-OFE Micro Gear Manufacturing Compared to Macro-scale Forming - Rohrmoser, Andreas; Kraus, Martin; Leicht, Miriam; Merklein, Marion (Manufacturing Letters, 2022)
The increasing miniaturization of technical systems leads to a rising demand for micro components. Miniaturized drive systems with geared micro parts or micro gears are applied in various industries. Due to the demand for high production volumes, productive and resource-efficient fabrication is of major importance. Compared to industrially applied manufacturing methods like cutting and metal powder injection, cold forming provides technological, economic and ecological potential for the mass production of micro gears. It enables high productivity and advantageous mechanical properties of the gears. In the macroscopic size range, forming processes are well established in series production of gears. However, in micro-scale, according to the current state of the art, cold forming of modules m < 0.2 mm is not possible due to size effects, high tool loads and handling problems. Within this contribution, a multi-stage forming process for the fabrication of micro gears with a module of m = 0.1 mm is introduced and compared with a conventional forming process on macro-scale with a module of m = 1.0 mm. The use of coil material provides potential for easy handling of the micro parts in a progressive die for the potential application in a high-speed press. In addition, the multi-stage forming achieves a grain alignment, which enhances the formation of the micro gear profile. Based on the comparison between micro- and macro-scale, the performance of the micro process is analyzed with regard to deviations of process force as well as gear quality and possible size effects are identified. The results prove the feasibility of the process chain and the achievement of equivalent part quality and reproducibility compared to macro-scale forming.<br

Experimental study of the potential for extending the process limits in multi-stage forming of micro gears from sheet metal by a local short-term laser heat treatment - Leicht, Miriam; Kraus, Martin; Rohrmoser, Andreas; Merklein, Marion (Materials Research Proceedings 2023, 2023)
Cold forming of micro gears is currently not possible for modules m < 0.2 mm due to the occurrence of high tool stresses, handling problems and size effects. A multi-stage process chain of micro bulk forming from sheet metal offers the potential to solve these challenges. However, the industrial applicability is limited due to material efficiency. Against this background, the aim of this research work is an improvement of the material utilization as well as a further reduction of the tool stresses. Therefore, the influence of different heat treatment strategies as well as the materials copper Cu-OFE and brass CuZn30 are analyzed. Thus, a local laser heat treatment and a global heat treatment of the blanks are investigated. The focus of this research work is on the first process stage, pin extrusion, which is used for forming of the wheel blank. Since this process setup provides the material for the further forming stages, it has a huge influence on the material efficiency and on the forming of the gearing in the second process stage. Therefore, the component and process properties are evaluated to assess the influence of the measures. The results prove higher material efficiency at a similar tool stress by using local short-term heat treatmen

Experimental Study on Joining by Forming of HCT590X+Z and EN-AW 6014 Sheets Using Cold Extruded Pin Structures - Römisch, David; Kraus, Martin; Merklein, Marion (Journal of Manufacturing and Materials Processing, 2021)
Due to stricter emission targets in the mobility sector and the resulting trend towards lightweight construction in order to reduce weight and consequently emissions, multi-material systems that allow a material to be placed in the right quantity and in the right place are becoming increasingly important. One major challenge that is holding back the rapid and widespread use of multi-material systems is the lack of adequate joining processes that are suitable for joining dissimilar materials. Joining processes without auxiliary elements have the advantage of a reduced assembly effort and no additional added weight. Conventional joining processes without auxiliary elements, such as welding, clinching, or the use of adhesives, reach their limits due to different mechanical properties and chemical incompatibilities. A process with potential in the field of joining dissimilar materials is joining without an auxiliary element using pin structures. However, current pin manufacturing processes are mostly time-consuming or can only be integrated barely into existing industrial manufacturing processes due to their specific properties. For this reason, the present work investigates the production of single- and multi-pin structures from high-strength dual-phase steel HCT590X + Z (DP600, t(0) = 1.5 mm) by cold extrusion directly out of the sheet metal. These structures are subsequently joined with an aluminium sheet (EN AW-6014-T4, t(0) = 1.5 mm) by direct pin pressing. For a quantitative evaluation of the joint quality, tensile shear tests are carried out and the influence of different pin heights, pin number, and pin arrangements, as well as different joining strategies on the joint strength is experimentally evaluated. It is proven that a single pin structure with a diameter of 1.5 mm and an average height of 1.86 mm achieves a maximum tensile shear force of 1025 N. The results reveal that the formation of a form-fit during direct pin pressing is essential for the joint strength. By increasing the number of pins, a linear increase in force could be demonstrated, which is independent of the arrangement of the pin structures.
CRIS-Team WoS Importer:2021-04-30

Forming of Components with Microgearings from Coil Material—Numerical Modeling of the Process Chain and Experimental Validation - Rohrmoser, Andreas; Kraus, Martin; Merklein, Marion (Micromachines, 2021)
Compared to alternative production methods, cold forming offers technological, economic and ecological potential for the mass production of microgears. Within the current boundaries of the technology, the cold forming of modules m < 0.2 mm is not possible due to size effects, high tool stresses and handling problems. The investigations of this contribution present a novel process chain for the multi-step forming of microgears with a module of m = 0.1 mm. For this purpose, a numerical model of the first two steps of the process chain is set up and confirmed based on experimental forming tests. The results have proven the feasibility of the process chain by a complete forming of the gear teeth.
Keywords: micro forming; microgear; sheet-bulk metal forming; multi-step micro forming

Grundlagenwissenschaftliche Untersuchungen zum Kaltfließpressen kleinster metallischer Pin-Strukturen aus der Blechebene - Kraus, Martin (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2024)
Die Miniaturisierung von Produkten bei gleichzeitiger Integration mehrerer Funktionen ist ein aktueller globaler Trend, um Gewicht, Platz, Material und Kosten zu sparen. Jedes Jahr werden Milliarden metallische Mikrobauteile produziert, und die Tendenz steigt. Umformtechnische Verfahren bieten bei der Massenproduktion technologische, wirtschaftliche und ökologische Vorteile gegenüber anderen Fertigungsverfahren. Bei der Verkleinerung in den Mikrobereich treten jedoch Größeneffekte auf, welche die Formgebung, die Prozessstabilität, die Handhabung und die Werkzeugbeanspruchung negativ beeinträchtigen können. Das mehrstufige Kaltfließpressen aus der Blechebene kann die Auswirkungen der Größeneffekte mindern, aber der komplexe Materialfluss bringt auch Herausforderungen mit sich. Daher war es das Ziel dieser Arbeit, ein grundlegendes Verständnis für den Prozess zu schaffen, um Ingenieuren bei der Optimierung zu helfen und den Übergang zu industriellen Anwendungen zu unterstützen. Im Rahmen der Untersuchungen dieser Arbeit konnte nachgewiesen werden, dass durch die mehrstufige Umformung wesentlich filigranere Pin-Strukturen aus der Blechebene hergestellt werden können. Zudem wurde aufgezeigt, dass durch die Auswahl geeigneter prozess-, werkstück-, und werkzeugseitiger Einflussparameter die Materialausnutzung erheblich gesteigert werden kann. Die gemachten Handlungsempfehlungen zur Prozessoptimierung und dargelegten Anwendungsmöglichkeiten sollen dazu beitragen, das Verfahren in der industriellen Produktion effizienter und nachhaltiger zu gestalte

Influence of Materials and Its Conditions on Pin-Extrusion from Sheet Metal - Kraus, Martin; Merklein, Marion (Lecture Notes in Mechanical Engineering, 2024)
Pin structures extruded from the sheet metal plane have numerous industrial applications. For instance, they can be used in bulk microforming to solve handling difficulties or in joining technology to connect dissimilar materials. Due to the absence of material flow restrictions in the direction of the sheet metal plane, pin extrusion is affected by numerous process-, workpiece- and tool-related parameters, which have a huge impact on the material utilization and the obtainable pin geometry. Within the scope of this study, a combined numerical-experimental research approach is used to analyze the influence of the material and its condition on the achievable pin height and the occurrence of the mostly undesired funnel formation at high punch penetration depths. For this purpose, elastic-ideal plastic and elastic-real hardening model materials are first investigated numerically, which are subsequently validated and verified in experiments by using the materials Cu-OFE, AA6016, DC04 on a laboratory scale. Based on the results, recommendations for the material selection and its properties are derived in order to maximize the material utilization.
Created from Fastlane, Scopus look-up
Keywords: extrusion; material flow; pin-extrusion; sheet metal

Investigation of Different Joining by Forming Strategies when Connecting Different Metals without Auxiliary Elements - Römisch, David; Kraus, Martin; Merklein, Marion (Sheet Metal 2021, 2021)
Lightweight constructions become more and more important, especially in the mobility sector. In this industry, the increasingly strict regulations regarding the emissions of carbon dioxide can be achieved to a certain extent by reducing the vehicle weight. Thus, multi-material systems are used. Conventional joining techniques reach their limits when joining different materials due to different thermal expansion, unequal stiffness or chemical incompatibilities. This is why additional joining elements or adhesives are used. These must be viewed critically regarding a lightweight and resource-efficient production, since they add weight or complicate the recycling process of these components. Consequently, there is a great and growing need for new versatile joining technologies in order to overcome these challenges and to be able to react to changing process parameters and boundary conditions. Joining without an auxiliary element using pin structures formed directly from the sheet metal plane is one approach to meet these challenges. These pin structures are then joined by direct pressing into the joining partner. This is possible with a variety of material combinations, but is advantageous with regard to continuous fibre-reinforced thermoplastic composites (CFRTP), as the fibres do not have to be cut when joining CFRTP using pin structures. In this paper, the formability of pin structures made of a dual-phase steel DP600 (HCT590X + Z) is investigated. The extruded pin structures are joined by direct pin pressing with an EN AW-6014 to form tensile shear specimens. Different joining strategies are investigated to compare their influence on the joint strength. The results have shown that it is feasible to form suitable pins from a DP600 dual-phase steel to produce reliable connections with an aluminium sheet joined by direct pin pressin
Keywords: joining by forming; multi-metal-systems; pin forming; pin joining

Investigation of Size Effects in Multi-Stage Cold Forming of Metallic Micro Parts from Sheet Metal - Kraus, Martin; Merklein, Marion (Micromachines, 2021)
Product miniaturisation and functional integration are currently global trends to save weight, space, materials and costs. This leads to an increasing demand for metallic micro components. Thus, the development of appropriate production technologies is in the focus of current research activities. Due to its efficiency, accuracy and short cycle times, microforming at room temperature offers the potential to meet the steadily increasing demand. During microforming, size effects occur which negatively affect the part quality, process stability, tool life and handling. Within this contribution, a multi-stage bulk microforming process from sheet metal is investigated for the materials Cu-OFE and AA6014 with regard to the basic feasibility and the occurrence of size effects. The results reveal that the process chain is basically suitable to produce metallic micro parts with a high repeatability. Size effects are identified during the process. Since several studies postulate that size effects can be minimised by scaling down the metallic grain structure, the grain size of the aluminium material AA6014-W is scaled down to less than one micrometre by using an accumulative roll bonding process (ARB). Subsequently, the effects of the ultrafine grain (UFG) structure on the forming process are analysed. It could be shown that a strengthened material state increases the material utilization. Furthermore, too soft materials can cause damage on the part during ejection. The occurring size effects cannot be eliminated by reducing the grain size.
CRIS-Team WoS Importer:2022-01-07

Investigation of the direct recyclability of chip waste by cold cup extrusion and identification of its potential in continuous processes - Zettl, Bastian; Kraus, Martin; Böhm, Wolfgang; Zippert, Patrick; Merklein, Marion (Forming Technology Forum 2022, 2022)
Environmental protection and the responsible use of natural resources are currently the main challenges facing our society. When machining metallic materials, the formation of chips is unavoidable caused by technological reasons. This leads to a large proportion of chip waste. This waste needs to be subsequently recycled in energy-intensive cleaning and melting processes. To face these, this work is dealing with a novel direct recyclability method of chips from technically pure aluminum EN AW-1050A and pure copper CW004A by cold cup extrusion. The cups are characterized in regard to their bonding quality by light microscopy and X-ray analysis in order to prove the feasibility of the method. The objective is to demonstrate the suitability of cold cup drawing for creating cohesive bonds even under varying chip properties. Additionally, the usage of chip waste for recycling without melting in a continuous forming process is analyzed. For this, the so called Temconex® method is introduced, which enables the production of semi-finished profiles by a combination of friction and severe plastic deformation in an extrusion process.<br
Keywords: recycling; chips; cyclic economy; extrusion; sustainability; aluminum; copper

Investigation of the Influence by Size Effects on the Material Characterization of the Uniaxial Compression Stress State - Hetz, Peter; Kraus, Martin; Merklein, Marion (Key Engineering Materials, 2022)
For the evaluation of final component properties under consideration of production-induced material characteristics, it is necessary to determine the mechanical parameters of parts and structures. Thus, there is a need of new test methods for the material characterization and quality control of produced goods. The miniaturization of the test specimens offers the potential for the local testing of the material properties at almost any position on the component. However, due to the reduction in size of the test specimens, size effects can occur which may affect the material behavior. For this reason, this contribution analyses the influence of size effects on the derived material parameters in dependence of the specimen size and material by using upsetting tests according to DIN 50106:2016 standard. The materials Cu-OFE (copper), X5CrNi18-10 (stainless steel) and AA7075-T6 (aluminum) are investigated to ensure a broad transferability of the findings. The specimens are cut from a bar stock by using a high precision 3D micro electrical discharge milling machining. Due to the small size, every specimen is measured with an optical 3D coordinate measuring system to determine the exact size. Through these investigations, the reproducibility and scatter in the determination of material properties for scaled cylindrical upsetting specimens are evaluated. Furthermore, limits of geometric dimensions at constant aspect ratios are derived. The results of this investigation enable an estimation of the geometrical influence of the specimen size in regard to the mechanical properties.
CRIS-Team Scopus Importer:2022-11-04
Keywords: Compression test; Material characterization; Miniaturization; Size effects

Investigation of the influence of formed, non-rotationally symmetrical pin geometries and their effect on the joint quality of steel and aluminium sheets by direct pin pressing - Römisch, David; Kraus, Martin; Merklein, Marion (Proceedings of the Institution of Mechanical Engineers Part L-Journal of Materials-Design and Applications, 2022)
Resource-saving and sustainable production is becoming increasingly important regarding social, political and economic aspects, thus making the use of lightweight-construction technologies a current trend. For this reason, multi-material-systems made of high-strength steel and aluminium as well as metal and fibre-reinforced plastics gain in importance. However, different material properties, e.g. stiffness, thermal expansion coefficients or chemical incompatibilities, are challenging for conventional joining technologies. Joining by cold formed pin structures has shown to have high potential for joining multi-material-systems. These pins can be joined either by direct pin pressing into an unperforated joining partner or by caulking, where the pins are inserted through a pre-punched joining partner and the pin head is upset, resulting in a form-fit joint. Usually, cylindrical pins are used for joining. However, non-rotationally symmetrical pin geometries offer the possibility of introducing a predetermined breaking point or reinforcing a connection in the principal force direction. In this work, cylindrical pins as well as non-rotationally symmetrical pin geometries, such as polygonal and oval pin structures, are cold extruded from the sheet metal plane of an HCT590X+Z dual phase steel and joined in the next step with an EN AW-6014 aluminium using direct pin pressing. Since the formation of an undercut has an crucial influence on the joint strength, the investigations will be focused on the resulting joint geometry. In addition, the effect of different pin heights will be examined to analyse the joint formation at different levels of compression of the pin structures. Finally, the joints are evaluated regarding their joint strength in tensile shear tests and cross tension tests. Here the flow resistance of the geometry used as well as the pin height and thus the strain hardening of the pin base during the extrusion of the pins play a decisive role for the shear strengt
Keywords: pin-joining; alternative pin geometries; joining by forming; versatile joining process

Investigation of the Influence of Formed, Non-rotationally Symmetrical Pin Geometries and their Effect on the Joint Quality of Steel and Aluminum Sheets by Direct Pin Pressing - Römisch, David; Kraus, Martin; Merklein, Marion (AJP2021, 2021)
Resource-saving and sustainable production is becoming increasingly important regarding social, political and economic aspects, thus making the use of lightweight construction technologies a current trend. For this reason, multi-material systems made of high-strength steel and aluminium as well as metal and fibre-reinforced plastics gain in importance. However, different material properties, e.g. stiffness, thermal expansion coefficients or chemical incompatibilities, are challenging for conventional joining technologies. Joining by using cold formed pin structures has shown to be a process with high potential for joining multi-material systems. These pin structures can be joined either by direct pin pressing into an unperforated joining partner or by caulking, where the pin structures are inserted through a pre-punched joining partner and the pin head is upset, resulting in a form fit joint. Usually, cylindrical pin structures are used for joining. However, non-rotationally symmetrical pin geometries offer the possibility of introducing a predetermined breaking point or reinforcing a connection in the principal force direction. In this work, cylindrical pin structures as well as non-rotationally symmetrical pin geometries, such as polygonal and oval pin structures, are cold extruded from the sheet metal plane of an HCT590X + Z dual phase steel and joined in the next step with an EN AW-6014 aluminium using direct pin pressing. Since the formation of an undercut is a crucial influence on the joint strength [1], the investigations will be focused on the resulting joint geometry. In addition, the effect of different pin heights will be examined in order to analyze the joint formation at different levels of compression of the pin structures. Finally, the joints are evaluated regarding their joint strength in tensile shear tests and cross tension test
Keywords: pin joining; mechanical joining; joining by forming

Investigation of the influence of material and sheet thickness on a three-stage process chain for cold forming of micro gears with a module of 0.1 mm - Leicht, Miriam; Rohrmoser, Andreas; Kraus, Martin; Merklein, Marion (The 19th International Conference on Metal Forming (MF 2022), 2022)
In many industries, there is a trend towards miniaturization of technical components, such as drive systems, which enable the solution of high-precision positioning tasks because of their low volume and high dynamics. Geared micro parts are currently mainly produced by cutting and LIGA processes, but in mass production cold forming offers ecological and economic benefits. However, the cold forming of micro gears is restricted to a lower module limit of m = 0.2 mm due to high tool stresses, size effects and handling difficulties. To solve these challenges, in this contribution a three-stage forming process chain for the manufacturing micro gears (m = 0.1 mm) is investigated. In the first stage, a pin as wheel blank is extruded from sheet metal, which is geared subsequently by lateral extrusion. Finally, the micro gear is separated from sheet by shear cutting. The aim of this study is to demonstrate the applicability of the process chain for the materials Cu-OFE and CuZn30. In addition, the influence of the sheet thickness, which has a major impact on the forming process and the material efficiency, is analyzed. The geometrical and mechanical component properties as well as the machine data are evaluated to assess the variable

Investigation of the joinability of single- and multi-layered AA6014 sheets produced by accumulative roll bonding in the shear-clinching process - Zettl, Bastian; Wiesenmayer, Sebastian; Kraus, Martin; Merklein, Marion (Proceedings of the Institution of Mechanical Engineers Part L-Journal of Materials-Design and Applications, 2022)
Accumulative roll bonding belongs to the severe plastic deformation processes and is suitable for producing multi-layered as well as high-strength sheets through repeated rolling. After four accumulative roll bonding-cycles, the strength of the investigated AA6014-T4 alloy is elevated due to strain and fine grain hardening by 170% in yield strength and by 37% in ultimate tensile strength. This is accompanied by a significant decrease in material ductility which is disadvantageous for joining processes based on forming operations. Shear-clinching, however, can be used to join high-strength and low-ductile materials on the die side. Thus, it is a promising method for the mechanical joining of accumulative roll bonding components. The multi-layered and more brittle material is located on the die side whereas the single-layered base material with higher ductility is positioned on the punch side. At present, there is no scientific knowledge how the multi-layered material behaves in the shear-clinching process. Since the material is cut in the process, delamination effects could occur at the interfaces produced via accumulative roll bonding. Additionally, the investigation aims at the influence of the accumulative roll bonding process on the properties of the joints. They are expected to depend on the number of process cycles and thus on the change of mechanical properties of the multi-layered material. The bond strength of the shear-clinched joints is determined by shear and tensile tests. The areas of material failure are analysed via metallographic methods. From the failure behaviour and load-bearing capacity it is determined which number of accumulative roll bonding cycles is ideal for joining multi-layered sheets via shear-clinching.
CRIS-Team Scopus Importer:2022-02-04
Keywords: accumulative roll bonding; Joining; multi-layered materials; shear-clinching

Investigation of the Potential for the Fabrication and Forming of Adaptronic Semi-finished Parts Joined by Cold Formed Pin Structures - Kraus, Martin; Suttner, Sebastian; Merklein, Marion (2ND INTERNATIONAL CONFERENCE ON ADVANCED JOINING PROCESSES (AJP 2021), 2021)

Mechanical joining without auxiliary element by cold formed pins for multi-material-systems - Kraus, Martin; Frey, Philipp; Kleffel, Tobias; Drummer, Dietmar; Merklein, Marion (22nd International ESAFORM Conference on Material Forming (ESAFORM 2019), 2019)

Modification of Tribological Conditions for Influencing the Material Flow in Bulk Forming of Microparts from Sheet Metal - Kraus, Martin; Andreas, Kolja; Stellin, Tommaso; Engel, Ulf; Merklein, Marion (AIP Conference Proceedings 1896, 2017)
LFT Import::2019-08-05 (2269)

Potential of Joining Dissimilar Materials by Cold Formed Pin-Structures - Kraus, Martin; Merklein, Marion (Journal of Materials Processing Technology, 2020)
Joining dissimilar materials brings established joining techniques to their limits due to different thermal expansion, unequal stiffness/strength and chemical incompatibilities. The use of pin-structures has proven an appropriate strategy to join multi-material-systems in laboratory scale. At present, the industrial application of this joining technology is limited due to the time-consuming pin manufacturing process and the inadequately researched achievable joint strengths. In this study, extrusion of the pin-structures from sheet metal is used to investigate an approach that can be directly integrated into existing production processes and does not require auxiliary joining elements. With direct-pin-pressing and caulking, two different joining strategies are analysed to join multi-material systems of sheet steel (DC04, t0 = 2 mm) and aluminium (EN AW 6016-T4, t0 = 2 mm). The basic feasibility of the joining technique is experimentally proven by using single-pin-structures. The joint strength is analysed by tensile shear tests, micro sections and failure patterns. Based on the experimental results, a failure criterion for the joint is defined. Parallel to the experiments, numerical finite element models (FE-models) for the single-pin-joint are developed and validated. In a further step, numerical investigations for multi-pin-structures are carried out in order to derive predictions on achievable joint strengths with this joining technique. It is shown that the form-fit is crucial for the joint strength. Thus, 93 % higher shear strength is achieved for caulked joints. By multi-pin-structures the strength can be increased considerably. For a 5 × 3 pin-structure, shear strength of 9.9 kN can be achieved.
CRIS-Team Scopus Importer:2020-05-22
Keywords: Forming; Joining; Multi-material-system; Pin extrusion

Potential of Joining Dissimilar Materials by Cold Formed Pin-Structures - Kraus, Martin; Merklein, Marion (AJP 2019, 2019)

Tailored material flow in pin-extrusion of sheet metal under varying material and geometric conditions for enhanced joining technology applications - Römisch, David; Kraus, Martin; Merklein, Marion (International Journal of Material Forming, 2025)
Pin structures extruded from the sheet metal plane have numerous industrial applications. For instance, they can be used in bulk microforming to solve handling difficulties or in joining technology to connect dissimilar materials to overcome challenges of different chemical, thermal and mechanical properties of materials. Due to the absence of material flow restrictions in the direction of the sheet metal plane, pin extrusion is affected by numerous process-, workpiece- and tool-related parameters, which have a huge impact on the material utilization and the obtainable pin geometry. Within the scope of this study, a combined numerical-experimental research approach is used to analyze the influence of the material and its condition on the achievable pin height and the occurrence of the mostly undesired funnel formation at high punch penetration depths. For this purpose, elastic-ideal plastic and elastic-real hardening model materials are first investigated numerically, which are subsequently validated and verified in experiments by using the materials Cu-OFE and DC04 on a laboratory scale. Based on the results, recommendations for the material selection and its properties are derived in order to maximize the material utilization. In addition, a pin joining process with locally modified extrusion conditions to increase the load-bearing capacity, especially under axial load, is being investigated with DP600 and AA 6014-T4. This process is a new type of two-stage mechanical joining process without an auxiliary joining element in which pin structures extruded from the sheet metal plane are used to join dissimilar materials in a subsequent step. In this work, test specimens are locally pre-punched before pin extrusion to create an enhanced pin geometry in order to achieve an improved undercut in the subsequent joining process. As a result, a new type of pin geometry was realized and investigated, which shows a significant increase of up to 82% in load-bearing capacity under axial load compared to the existing reference pin geometr
Keywords: Pin extrusion; Material flow; Pin-joining; Sheet metal

Verification of the Accuracy of FE-Models in Bulk-Forming of Micropins from Sheet Metal - Kraus, Martin; Hufnagel, Thomas; Merklein, Marion (WCMNM 2018 World Congress on Micro and Nano Manufacturing, doi: 10.3850/978-981-11-2728-1_02, 2018)
LFT Import::2019-08-07 (2307)

Verification of the Accuracy of FE-Models in Bulk-Forming of Micropins from Sheet Metal - Kraus, Martin; Hufnagel, Thomas; Merklein, Marion (World Congress on Micro and Nano Manufacturing - WCMNM 2018, 2018)

Warmforming Flow Pressing Characteristics of Continuous Fibre Reinforced Thermoplastic Composites - Gröger, Benjamin; Römisch, David; Kraus, Martin; Troschitz, Juliane; Füßel, René; Merklein, Marion; Gude, Maik (Polymers, 2022)
The paper presents research regarding a thermally supported multi-material clinching process (hotclinching) for metal and thermoplastic composite (TPC) sheets: an experimental approach to investigate the flow pressing phenomena during joining. Therefore, an experimental setup is developed to compress the TPC-specimens in out-of-plane direction with different initial TPC thicknesses and varying temperature levels. The deformed specimens are analyzed with computed tomography to investigate the resultant inner material structure at different compaction levels. The results are compared in terms of force-compaction-curves and occurring phenomena during compaction. The change of the material structure is characterized by sliding phenomena and crack initiation and growt
Keywords: thermoplastic composite; clinching; joining; material behaviour; FEM; compaction